2012
DOI: 10.1002/alr.21099
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe epistaxis after Young's procedure: a case report

Abstract: We report a case of significant, life-threatening epistaxis following a modified Young's procedure that requiring multiple transfusions, bilateral embolization, and ultimately reversal of the Young's procedure for control of epistaxis. Although recognized as a potential complication, to our knowledge this is the first report in the English literature of such a case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Conventional therapies used in the management of HHT‐related epistaxis, such as laser coagulation, septodermoplasty, selective arterial embolization, and Young's occlusion, each have specific associated complications, including worsened epistaxis, septal perforation, foul odor, nasal crusting, and compromised nasal breathing . Moreover, intranasal Bevacizumab is also a promising treatment option but presents the potential for impaired wound healing in the context of an otherwise unproven side‐effect profile …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional therapies used in the management of HHT‐related epistaxis, such as laser coagulation, septodermoplasty, selective arterial embolization, and Young's occlusion, each have specific associated complications, including worsened epistaxis, septal perforation, foul odor, nasal crusting, and compromised nasal breathing . Moreover, intranasal Bevacizumab is also a promising treatment option but presents the potential for impaired wound healing in the context of an otherwise unproven side‐effect profile …”
Section: Discussionmentioning
confidence: 99%
“…However, it has been long hypothesized and has been recently reported that management of epistaxis in a patient with closed nostril(s) can be exceedingly difficult without reversal of the procedure. In fact, Ting et al . reported a case in which a patient who had previously undergone Young's procedure with initial successful postoperative symptom reduction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Posterior epistaxis can occur and may be difficult to treat due to loss of access via the nares as reported by the case of a 70 year old woman who required multiple transfusions, intubation, bilateral embolization, and reversal of nasal closure. 19 Thankfully this is rare, and our experience has been nearly immediate cessation of bleeding after the procedure. In addition to discussion of these side effects we recommend a trial of functional closure using petroleum jelly-soaked cotton balls placed in the nares.…”
Section: Discussionmentioning
confidence: 91%
“…The lack of smell and taste was the most frequent complaint. In the literature, there are some isolated cases of bleeding persistent despite the procedure, requiring a reopening of the nasal cavities 51 . In our experience, it is not so easy to convince the patients to undergo the procedure because nasal obstruction is badly supported.…”
Section: «Young's Procedure» -Nasal Closurementioning
confidence: 99%